Pengaruh Citra Merek, Harga Dan Kualitas Produk Smartphone Oppo Terhadap Keputusan Pembelian (Konsumen Siswa/I Smk Muhammadiyah 5 Kisaran) - Durahman Marpaung; Surya Bakti; Liza Saragih (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2021)
The purpose of the study was to analyze the magnitude of the influence of Brand Image, Price and Product Quality on Consumer Purchase Decisions on OPPO Smartphones, especially Students / I SMK Muhammadiyah 5 Research Range the author uses descriptive quantitative methods and tends to use theoretical basis analysis as a support that is formed to clarify a data. And data collection techniques using questionnaires, literature studies and interviews, while data analysis techniques use methods (validity test, reliability test), analysis test (descriptive test, classical assumption test, normality test, heteroscedasticity test), hypothesis test (multiple linear test, F test, T test, determination test).